Dialect contact and distinctiveness: The social meaning of language variation in an island community. (February 2015) - Moore, Emma; Carter, Paul
Abstract : In this paper, we analyse linguistic variables which are well‐established in British English, the vowels in thetrap andbath lexical sets. We demonstrate that the social meanings of these variables are both historically substantiated and locally‐elaborated. Our data is taken from the speech of individuals living on the Isles of Scilly, a group of islands off the south‐west coast of England. Our initial analysis shows thattrap andbath variants found on the islands are linked to contact with Standard English English, on the one hand, and the nearest neighbouring variety of Cornish English, on the other. The general distribution of variants is shown to reflect educational differences amongst our speakers. However, two case studies show speakers using forms atypical of their education type in order to position themselves in interactionally‐dynamic ways. This reveals how speakers exploit the multidimensional meanings of linguistic variants to reflect and construct local practices and alignments.